Factors influencing contraceptive choice: study focused on Czech men - Capova, Adela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The man’s participation in family planning appears as a suitable means for improvement of relationships between couples and their children. Gender sensitive breeding is a good way for supporting responsibility in family planning between man and woman and leads them in equal negotiation in questions of parenting. The purpose of research is to monitor contraception strategies and conditions affecting the timing of parenthood. Methods: Data were collected by interviews with 170 Czech men aged between 25 and 50. Grounded theory approach was used to generate new related theoretical ideas. Results: The present young men leave the decision rather up to women. A number of young men enter a relationship assuming automatically that their partner uses hormonal contraception. Family planning decision-making is influenced by personal values as well as structural factors. Strong social pressure determining the ideal form of material and psycho-social background for offspring confronts current generation with very demanding decision-making on parenthood timing. Conclusions: In men’s opinion, the setting of conditions for the beginning of reproduction should be the result of negotiation within the couple. Although men speak of the need to negotiate, the responsibility and practical decision-making is left up mainly to women.